EVALUATION OF FACTORS FOR ORAL HEALTH IN RELATION TO PYELONEPHRITIS IN CHILDHOOD - Sirma Angelova (Peytchinski Publishing, 2020)
Purpose: The aim of this study is to be evaluated factors related to oral health in children with diagnosed pyelonephritis. Material/Methods: A number of 92 children suffering from pyelonephritis and 41 healthy children participate in the research. A combination of clinical, statistical and sociological methods is implemented into the study. Results: The average value of the number of carious lesions in children with pyelonephritis amounts to 5,59, and the maximal value of the same indicator equals to 20. In comparison, the average value of the number of carious lesions among healthy children is 4,85 and the maximal value of that parameter is 13. The maximal value of GI Lõe-Silness is 2,00 in the group of participants with pyelonephritis, compared to 1,68 in healthy children. Almost 1/2 of the participants with the diagnosis pyelonephritis, namely 45,65%, performed dental visits only in an emergency. More than 1/2 of the healthy children, namely 65,85%, took part in regular dental visits on every six months. In the group of children suffering from pyelonephritis predominated the total ratio of parents with primary and basic education and illiterate parents. More than 2/3 of the parents of healthy children were characterized by higher education. Conclusions: The renal disease of pyelonephritis afflicts oral-dental health in childhood. Precise control of the common health disorder parallel to a thorough evaluation and adequate management of the oral-dental status of the individual determine the specific principles of optimization and performance of primary, secondary and tertiary prophylactic cares in the context of personalized medicine.